Internal hernia secondary to laparoscopic adjustable gastric band connecting tube loop - Girão de Caires, Francisco; Nunes, Mafalda; Flores, Priscila; Carvalhinha, Carolina; G. Caires, António; Loureiro, Rita (International Surgery Journal, 2025)
Laparoscopic adjustable gastric banding (LAGB) has been a widely used surgical technique for the management of morbid obesity. This report presents the case of a 70-year-old woman who developed small bowel obstruction (SBO) due to an incarcerated internal hernia, a rare complication of LAGB, caused by the connecting tube. The condition was successfully managed with urgent laparoscopy. As the use of LAGB continues to decline worldwide, such complications may become even rarer.